Integration of Information Communication Technology into Geography Instruction in Public Secondary Schools in Kenya. Mythical or Reality? - Wanjara, Amos Otieno; Ogembo, Paul Okeyo (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Informational Communication and Technology (ICT) falls under the learner-centered strategy and is likely to improve learner interest and achievement. This is in tandem with the Kenyan government’s ICT policy of 2007. The study aimed to assess the extent of ICT integration into geography instruction in Kenya's public secondary schools. The study aimed to determine the institutional factors that influence the integration of ICT into geography teaching, the factors of geography teachers that influence the integration of ICT into geography teaching and learning, and the factors of students that influence the integration of ICT into geography teaching and learning in public secondary schools in Migori County, Kenya. Davis (1989) anchored the study on the technology acceptance model. The study also used a meta-analysis of empirical literature, guided by Ferrer (1998). The study found that institutional, teacher, and student factors impacted the integration of ICT into teaching and learning geography in public secondary schools in Migori County, Kenya. These findings have implications for schools' integration of ICT policy into geography instruction.